Pengaruh Penerapan Akuntansi Pemerintahan Dan Pengawasan Kualitas Laporan Keuangan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Provinsi Sumatera Utara Pada Badan Keuangan Dan Aset Daerah - Muhammad Syahputra Rizki; Novien Rialdy (JURNAL LENTERA BISNIS, 2023)
This study aims to determine the effect of implementing government accounting and monitoring the quality of financial reports on performance accountability of North Sumatra provincial government agencies in regional financial and asset bodies and to determine the effect partially or simultaneously on the regional financial and asset offices of North Sumatra province. The approach used in this research is a descriptive and associative quantitative approach. The population in this study are all Regional Financial and Asset Agency Work Units within the scope of the North Sumatra Provincial Government. The data collection technique in this study used a questionnaire technique in the form of a Gform. Data processing in this study used the SPSS (Statistics Package for the Social Sciences) software version 29.0. These results indicate that the application of government accounting has a significant effect on the accountability of Government Agency Performance in the regional financial and asset agency offices of North Sumatra Province. the performance of government agencies in the regional financial and asset agency offices of North Sumatra Province, this is due to the higher t-count value than t-table and the application of government accounting and monitoring the quality of financial reports affects the performance accountability of government agencies in the offices of financial and asset bodies of North Sumatra Province as seen from the f-count value which is higher than the f-table.Keywords: Implementation of Government Accounting, Quality Control of Financial Statements, Performance Accountability of Government Agencies.